Exploring the Relationship between Body Shaming and Self-Concept among Adolescents - Ani Nurhaeni; Dewi Erna Marisa; Thia Oktiany; Rosalia Rahayu; Endah Sari Purbaningsih; Lili Wahyuni (GLOBAL HEALTH SCIENCE GROUP, 2025)
Body shaming is a pervasive issue with significant psychological consequences, particularly among adolescents. As adolescents undergo various physical and emotional changes, the pressures of social comparison and body image often lead to negative impacts on their self-concept. This study explores the relationship between body shaming and self-concept among adolescents in Cirebon, Indonesia.Methods:A cross-sectional design was used in this study, This study used total sampling, involving 180 students aged 12–16 years. Data were collected using a structured questionnaire that assessed participants' experiences with body shaming and their self concept, including self-esteem, self-identity, and physical appearance satisfaction. The questionnaire had previously undergone validity and reliability testing in a different school setting to ensure its accuracy and consistency.The analysis was conducted using Pearson’s correlation and regression analysis to examine the relationship between body shaming and self-concept.Results: The findings indicate a significant negative correlation between body shaming experiences and self-concept. As body shaming experiences increased, adolescents reported lower levels of self-esteem, self-identity, and satisfaction with their physical appearance. These results highlight the psychological toll of body shaming and its negative influence on adolescent self-concept.Conclusion:This study provides strong evidence that body shaming negatively impacts adolescents’ self-concept. These findings underscore the importance of addressing body shaming through interventions aimed at fostering self-acceptance, body positivity, and resilience among adolescents, particularly within school settings.